2022
DOI: 10.3389/fonc.2022.848485
|View full text |Cite
|
Sign up to set email alerts
|

Primary Neuroendocrine Tumor of the Breast: Current Understanding and Future Perspectives

Abstract: Primary neuroendocrine carcinoma of the breast (NECB) is characterized with heterogeneity, rarity, and poor differentiation, which is probably an underestimated subtype of breast cancer, including small cell NECs and large cell NECs. The diagnostic criteria for NECB have been constantly updated as the disease changes and the understanding increases. According to the latest WHO Classification, primary neuroendocrine neoplasm (NEN) of the breast consists of well-differentiated neuroendocrine tumors (NET), extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…It is our venture to speculate whether the development of neuroendocrine carcinoma components is related to metaplastic carcinoma and whether it is a speci c type of metaplastic carcinoma that has not been reported. We consider whether this conjecture can be veri ed with the help of molecular assays and other methods, and it has been shown that a certain percentage of PIK3CA mutation rate exists in both NECB and MpBC [1,5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is our venture to speculate whether the development of neuroendocrine carcinoma components is related to metaplastic carcinoma and whether it is a speci c type of metaplastic carcinoma that has not been reported. We consider whether this conjecture can be veri ed with the help of molecular assays and other methods, and it has been shown that a certain percentage of PIK3CA mutation rate exists in both NECB and MpBC [1,5] .…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine carcinoma of the breast (NECB) is a rare clinical cancer with neuroendocrine morphology, immunophenotype, and high-grade cytological features, including small cell neuroendocrine carcinoma (SCNEC) and large cell neuroendocrine carcinoma (LCNEC). NECB is characterized by heterogeneity, rarity, and poor differentiation [1] . To date, the mechanisms, molecular changes, clinicopathological features, and prognosis of NECB are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The histological origin of BNEN is still unclear but the latest data postulates two theories. Some researchers propose that these tumours arise due to differentiation in breast cancer cells as NE cells have not been found in breast tissues, while another school of thought suggests NE cell proliferation in breast parenchyma in isolated clusters may be related to some precancerous states [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis for these primary carcinomas is essentially metastasis from NECs at other sites. Presence of DCIS and the absence of tumours in other organs in radiology help in clinching the diagnosis of primary NEC of the breast [ 10 ]. In the current case, DCIS was not found, however, there were no symptoms or radiological findings suggesting metastasis from other organs.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of high-quality data regarding therapeutic options in patients with disease progression of neuroendocrine carcinoma of the breast ( 58 ). Neuroendocrine carcinoma follows a more aggressive course than ductal carcinoma ( 57 , 59 ).…”
Section: Discussionmentioning
confidence: 99%